Parsing the Role of PPARs in Macrophage Processes - Toobian, Daniel; Ghosh, Pradipta; Katkar, Gajanan D. (Frontiers in Immunology, 2021)
Cells are richly equipped with nuclear receptors, which act as ligand-regulated transcription factors. Peroxisome proliferator-activated receptors (PPARs), members of the nuclear receptor family, have been extensively studied for their roles in development, differentiation, and homeostatic processes. In the recent past, there has been substantial interest in understanding and defining the functions of PPARs and their agonists in regulating innate and adaptive immune responses as well as their pharmacologic potential in combating acute and chronic inflammatory disease. In this review, we focus on emerging evidence of the potential roles of the PPAR subtypes in macrophage biology. We also discuss the roles of dual and pan PPAR agonists as modulators of immune cell function, microbial infection, and inflammatory diseases.